2018
DOI: 10.1016/j.ajog.2017.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Contraception after medication abortion in the United States: results from a cluster randomized trial

Abstract: BACKGROUND Understanding how contraceptive choices and access differ for women having medication abortions compared to aspiration procedures can help to identify priorities for improved patient-centered postabortion contraceptive care. OBJECTIVE The objective of this study was to investigate the differences in contraceptive counseling, method choices, and use between medication and aspiration abortion patients. STUDY DESIGN This subanalysis examines data from 643 abortion patients from 17 reproductive heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
2
12
0
7
Order By: Relevance
“…The higher use of injectable methods might be due to their popularity, simplicity of use, and availability . Women want more freedom at the time of choosing a contraceptive method and planning pregnancy, aiming to promote self‐care . Similar to other post‐abortion surveillance programs that have promoted a reduction in unplanned pregnancy over the years, such as those initiated in the United States in 1969, and in Ethiopia in 2010, the present study demonstrated an increased chance of starting contraceptive use after the establishment of the MUSA Network at the study hospital.…”
Section: Discussionsupporting
confidence: 50%
“…The higher use of injectable methods might be due to their popularity, simplicity of use, and availability . Women want more freedom at the time of choosing a contraceptive method and planning pregnancy, aiming to promote self‐care . Similar to other post‐abortion surveillance programs that have promoted a reduction in unplanned pregnancy over the years, such as those initiated in the United States in 1969, and in Ethiopia in 2010, the present study demonstrated an increased chance of starting contraceptive use after the establishment of the MUSA Network at the study hospital.…”
Section: Discussionsupporting
confidence: 50%
“…Increasing use of medical abortion and home administration of misoprostol as well as self‐assessment of the outcome of the abortion complicate contraceptive provision, especially LARC. Fewer US women having medical abortion had an intrauterine device insertion compared with those undergoing surgical abortion . Initiation of LARC is being explored at ever earlier intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Fewer US women having medical abortion had an intrauterine device insertion compared with those undergoing surgical abortion. 31 Initiation of LARC is being explored at ever earlier intervals. There are theoretical concerns about a possible interaction between progestins and the anti-progesterone mifepristone used for medical abortion.…”
Section: Contraception After Induced Abortionmentioning
confidence: 99%
“…Os estudos incluídos apresentaram um elevado nível de qualidade (Tabela 1), score superior ou igual a 7 (seis com score 10, dois com 9, um com 8 e dois com 7). Dos artigos elegíveis para análise verificou-se que os estudos pretenderam: descrever as caraterísticas da população (Tomnay et al, 2018); os resultados de intervenções em aconselhamento contracetivo no pós-aborto (Benson et al, 2018;Tomnay et al, 2018;Wendot et al, 2018); compará-los com as taxas de gravidezes não desejadas (Madden et al, 2019); as estratégias para o melhor aconselhamento contracetivo (Stembile, Kassouta, Sebikali, Lundstrom, & Saade, 2016;Che et al, 2017); aconselhamento realizado pelos profissionais de saúde em torno da contraceção e dos métodos contracetivos (Merki-Feld, Caetano, Porz, & Bitzer, 2018); a sua avaliação no pós-IVG (Tang et al, 2017); descrever a taxa de adesão à contraceção após aborto e os fatores que condicionam essa adesão (Pearson et al, 2017); relação entre o fornecimento de contracetivos após a IVG e a sua adesão (Laursen, Stumbras, Lewnard, Haider, & Laursen, 2017); diferenças no aconselhamento contracetivo e as escolhas de um método no pós-IVG (Rocca et al, 2018).…”
Section: Resultsunclassified